Female partners of opioid-injecting men in the Republic of Georgia: an initial characterization - Lund, Ingunn O (BioMed Central, 2012)
BACKGROUND: HIV and Hepatitis C virus (HCV) infections are strongly related to injection drug use in the Republic of Georgia. Little information is available about HIV and HCV status, sexual risk, support for their partner, and risk for physical violence among the female partners of opioid-injecting men in the Republic of Georgia, many of whom may not be using drugs, yet may be at high risk of being infected with HIV and HCV from their drug-using partners. METHODS: In order to better understand the risks for females whose partners are injecting drugs, the present study conducted an initial investigation of the non-substance-using female partners of 40 opioid-injecting men who were participating in a clinical trial examining the feasibility and efficacy of a 22-week comprehensive intervention that paired behavioral treatment with naltrexone. The 40 female partners were assessed at their male partners’ study intake. RESULTS: The female sample was 32.3 years old (SD=6.7), 37 (93%) were married, with 15.5 years of education. A majority reported at least partial employment the majority of the time during the past 3 years, with only one woman reported being unemployed most of the time during the past 3 years. They self-reported they were 3% HIV-positive and 8% HCV-positive. Their HIV sex risk scores indicated a relatively low risk. However, only 4 (10%) women reported using a condom most of the time while having sex and 15 (38%) report not having had sex during the last 30 days. Experiences of interpersonal violence were common, with 42% reporting physical abuse by their partner during the last year and 48% reporting feeling unsafe in their current relationship. CONCLUSIONS: The alarmingly high rate of failure to use barrier protection methods, together with the high percentage who did not know their HIV and HCV status, suggest that it may be beneficial to include non-substance-using female partners in prevention programs along with their partners to reduce the risk of HIV and HCV spreading from the population of injection-drug–using males into the general population. [This secondary analysis study was funded by an international supplement to the parent randomized clinical trial “Treating the Partners of Drug Using Pregnant Women: Stage II (HOPE)”. ClinicalTrials.gov Identifier: NCT00496990.]